ENTREPRENEURIAL EDUCATION AND IT’S IMPACT ON ENTREPRENEURIAL INTENTION: ENTREPRENEURIAL SELF-EFFICACY AS MEDIATING VARIABLE - Luh Made Noviady Mahaputri; Luh Made Noviady Mahaputri, I Gusti Ayu Manuati Dewi (Adisam Publisher, 2025)
University graduates contribute to the unemployment rate of 13.33 percent In Indonesia. Entrepreneurship is one of the solutions for a country, not only to overcome the problem of unemployment, but also to increase the country's economic growth. Entrepreneurial intention is able to encourage students to have the desire to start a business. To foster that desire, entrepreneurial education is given to students as a prefix to their introduction to the world of entrepreneurship. The higher the development of student knowledge in entrepreneurship, the faster the decline in unemployment in a country, so that economic growth is achieved. The purpose of this study is to analyze the effect of entrepreneurial education on entrepreneurial intention through entrepreneurial self-efficacy as mediating variable. This research was conducted in Faculty of Agricultural Technology, Udayana University- Denpasar-Bali-Indonesia with a sample of 85 students who were determined purposively. Data were collected using Google Form questionnaires. Data analysis techniques used were descriptive and inferential analysis. The results show that entrepreneurial education and entrepreneurial self-efficacy have a positive and significant effect on entrepreneurial intention, entrepreneurial education has a positive and significant effect on entrepreneurial self-efficacy, and entrepreneurial self-efficacy mediates the effect of entrepreneurial education on entrepreneurial intention. The theoretical implications of this research that is the findings confirm theory referred to in this study-Theory of Planned Behavior. In addition, practically, this research is able to be a consideration for the Faculty management in developing the potential of students to become young entrepreneurs through programs related to increasing entrepreneurial intentions.